An investigation of flow boiling with secondary flow interaction in curved pipes - Chandratilleke, Tilak; Nadim, Nima; Narayanaswamy, Ramesh (World Scientific, 2012)
This paper presents an investigation on flow boiling within curved pipes, where pipe curvature intrinsically produces secondary flow and hence, fundamentally different flow characteristics compared to straight pipes. For this boiling process influenced by secondary flow effects, the study develops a novel three-dimensional simulation methodology based on a non-equilibrium model with Eulerian multi-phase approach. It incorporates an incompressible multi-phase turbulent solver with k-ε model for excellent integrity off predicted results and considerable computational advantage. The model is tested for numerical stability and validated against reported experimental results. The flow regimes and temperature fields are obtained for flow boiling in curved pipes and compared with those in straight ducts with an analysis on observed differences in fluid and thermal characteristics. The study evaluates individual wall heat flux components that make up the overall heat transfer, namely that from liquid evaporation, quenching, single phase liquid and single phase vapour. These are effect timely used for illustration and physical interpretation of the unique effects from pipe curvature on the flow boiling process. The study also discusses the parametric influence from liquid sub-cooling, wall heat flux and centrifugal forces on flow patterns and, the onset of flow boiling in curved pipes along with the phase change and associated heat transfer.